MicroRNA‐transcription factor interactions and their combined effect on target gene expression in colon cancer cases. Issue 4 (29th December 2017) - Mullany, Lila E.; Herrick, Jennifer S.; Wolff, Roger K.; Stevens, John R.; Samowitz, Wade; Slattery, Martha L.
Abstract: Transcription factors (TFs) and microRNAs (miRNAs) regulate gene expression: TFs by influencing messenger RNA (mRNA) transcription and miRNAs by influencing mRNA translation and transcript degradation. Additionally, miRNAs and TFs alter each other's expression, making it difficult to ascertain the effect either one has on target gene (TG) expression. In this investigation, we use a two‐way interaction model with the TF and miRNA as independent variables to investigate whether miRNAs and TFs work together to influence TG expression levels in colon cancer subjects. We used known TF binding sites and validated miRNA targets to determine potential miRNA‐TF‐TG interactions, restricting interactions to those with a TF previously associated with altered risk of colorectal cancer death. We analyzed interactions using normal colonic mucosa expression as well as differential expression, which is measured as colonic carcinoma expression minus normal colonic mucosa expression. We analyzed 3518 miRNA‐TF‐TG triplets using normal mucosa expression and 617 triplets using differential expression. Normal colonic RNA‐Seq data were available for 168 individuals; of these, 159 also had carcinoma RNA‐Seq data. Thirteen unique miRNA‐TF‐TG interactions, comprising six miRNAs, four TFs, and 11 TGs, were statistically significant after adjustment for multiple comparisons in normal colonic mucosa, and 14 unique miRNA‐TF‐TG interactions, comprising two miRNAs, two TFs, and 13 TGs, were found for carcinoma‐normal differential expression. Our results show that TG expression is influenced by both miRNAs as well as TFs, and the influence of one regulator impacts the effect of the other on the shared TG expression.